Dialkylphosphinic acid hybrid salts, method for producing the same, and use thereof
A dialkylphosphinic acid hybrid salt with a specific composition formula (I) addresses the limitations of existing dialkylphosphinate salts by achieving high flame-retardant efficiency and thermal stability, suitable for a wide range of polymer materials, including those requiring high-temperature processing.
Patent Information
- Application Number
- JP2024521757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-15
- Publication Date
- 2025-05-28
- Estimated Expiration
- 2041-10-15
AI Technical Summary
Existing dialkylphosphinate salts, such as aluminum diethylphosphinate and aluminum diisobutylphosphinate, have limited flame-retardant efficiency and adverse effects on the physical properties of polymer materials, particularly at high temperatures and in polyester applications.
A dialkylphosphinic acid hybrid salt with a specific composition formula (I), where M is a central metal atom, diethylphosphinate, ethylisobutylphosphinate, and diisobutylphosphinate act as ligands, and the metal element is selected from Group IIA, IIIA, IVA, VA, transition metals, and lanthanides, with carefully controlled ratios of x, y, and z to optimize flame retardancy and thermal stability.
The hybrid salt achieves high flame-retardant efficiency with a small addition amount, excellent thermal stability, and economic efficiency, effectively addressing the limitations of existing dialkylphosphinate salts across various polymer materials, including those requiring high-temperature processing.
Smart Images

Figure 0007684670000029 
Figure 0007684670000030 
Figure 0007684670000031
Abstract
Description
Technical Field
[0001] The present application relates to a dialkylphosphinic acid hybrid salt, a method for producing the same, and use thereof, and belongs to the field of production of flame-retardant polymer materials.
Background Art
[0002] Dialkylphosphinate salts, especially aluminum diethylphosphinate, are widely used as halogen-free flame retardants for polymer materials. Dialkylphosphinate-based flame-retardant products have a low density, a small amount of flame retardant used, and good mechanical properties. However, existing dialkylphosphinate salts have limited flame-retardant efficiency as flame retardants. For example, polydialkylphosphinate can be used as a flame retardant for glass fiber-reinforced nylon without, but has a low flame-retardant efficiency and may have a great adverse effect on the physical properties of the flame-retardant polymer material during use. There is also a report on using aluminum diisobutylphosphinate for flame-retardant of nylon. Although aluminum diisobutylphosphinate has a very high flame-retardant efficiency, it has low thermal stability and begins to decompose and volatilize in large quantities at 300 °C, which is disadvantageous for engineering plastics that require high-temperature processing. In addition, aluminum diisobutylphosphinate has a poor flame-retardant effect on polyester. Also, due to its high plasticity, it is disadvantageous for the physical properties of the flame-retardant polymer.
Summary of the Invention
Problems to be Solved by the Invention
[0003] In order to solve the above technical problems, the present application provides a dialkylphosphinic acid hybrid salt having a composition of formula (I), a method for producing the same, and use thereof, which have a small addition amount, high flame-retardant efficiency for various polymer materials, and excellent economic efficiency.
Means for Solving the Problems
[0004] According to the first aspect of the present application, there is provided at least one dialkylphosphinic acid hybrid salt selected from compounds having the chemical formula shown in formula (I),
Chemical formula
[0005] In the examples of the present application, in formula (I), when y is less than 0.05, the flame retardant effect is not good. When y is greater than 0.8, the manufacturing cost is high, the economic efficiency is poor, and the thermal stability of the dialkylphosphinic acid hybrid salt decreases, which is disadvantageous for the manufacture and physical properties of the flame retardant polymer material. When x is greater than 0.95, the flame retardant properties are not good. When z is greater than 0.5, the manufacturing cost is high, the economic efficiency is poor, and the thermal stability decreases, which is disadvantageous for the manufacture and physical properties of the flame retardant polymer material.
[0006] Optionally, the lower limit of x is independently selected from 0, 0.15, 0.2, 0.25, 0.3, 0.35, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.03, and the upper limit is independently selected from 0.95, 0.9, 0.85, 0.87, 0.7.
[0007] Optionally, the lower limit of y is independently selected from 0.05, 0.1, 0.15, 0.2, 0.13, 0.29, and the upper limit is independently selected from 0.8, 0.7, 0.6, 0.5, 0.4, 0.35, 0.3, 0.25, 0.68.
[0008] Optionally, the lower limit of z is independently selected from 0, 0.02, and the upper limit is independently selected from 0.5, 0.45, 0.4, 0.35, 0.3, 0.25, 0.2, 0.15, 0.1, 0.05.
[0009] Optionally, the Group IIA metal element is at least one selected from Be, Mg, Ca, Sr, Ba, the Group IIIA metal element is Al, the Group IVA metal element is Sn, the Group VA metal element is Sb, the transition metal element is at least one selected from Fe, Zn, Cu, Ti, Zr, Mn, the lanthanide metal element is Ce.
[0010] Optionally, the metal element is at least one selected from Al, Zn, Ca, Fe.
[0011] Optionally, the metal element is Al and n = 3.
[0012] Optionally, 0.03 ≦ x ≦ 0.87, 0.13 ≦ y ≦ 0.68, and 0 ≦ z ≦ 0.45.
[0013] Optionally, 0.03 ≦ x ≦ 0.7, 0.29 ≦ y ≦ 0.68, and 0.01 ≦ z ≦ 0.45.
[0014] Optionally, 0.5 ≦ x ≦ 0.7, 0.29 ≦ y ≦ 0.48, and 0.01 ≦ z ≦ 0.21.
[0015] In the examples of the present application, the larger the z value, the earlier the thermal weight loss of the dialkylphosphinic acid hybrid salt becomes.
[0016] The dialkylphosphinic acid hybrid salt in the present application is not a simple physical mixture of different dialkylphosphinates. For example, it is not a mixture simply obtained by mixing aluminum diethylphosphinate and aluminum ethylisobutylphosphinate, but may contain diethylphosphinate ions, ethylisobutylphosphinate ions, and diisobutylphosphinate ions that pair with the same aluminum atom. The X-ray diffraction spectra (XRD) of these hybrid salts are very different from the XRD spectra of simple physical mixed salts of dialkylphosphinates. The dialkylphosphinic acid hybrid salt having the composition of formula (I) shows a single peak or overlapping double peaks in the region of the strongest absorption peak in the XRD spectrum. Also, the interplanar spacing of the crystal plane indicated by the maximum peak is different between aluminum diethylphosphinate and aluminum diisobutylphosphinate. The maximum peak of aluminum diethylphosphinate shows an interplanar spacing d = 9.663, and the maximum peak of aluminum diisobutylphosphinate shows an interplanar spacing d = 12.084. On the other hand, the value of the interplanar spacing d of the dialkylphosphinic acid hybrid salt having formula (I) exists between the above two. Even in the case of overlapping double peaks, the values of their d indicate that they are not pure aluminum diethylphosphinate or aluminum diisobutylphosphinate. However, a simple physical mixed salt obtained by mixing aluminum diethylphosphinate and aluminum diisobutylphosphinate shows two completely independent peaks in the XRD spectrum, and moreover, the values of their d are close to the d values of aluminum diethylphosphinate and aluminum diisobutylphosphinate, respectively.
[0017] In the examples of the present application, when a dialkylphosphinic acid hybrid salt having the composition of formula (I) and aluminum diethylphosphinate are simply physically mixed, two independent peaks appear in their XRD spectra. These results strongly indicate that the dialkylphosphinic acid hybrid salt having the composition of formula (I) obtained according to the present invention is not a simple mixture of aluminum diethylphosphinate, aluminum ethylisobutylphosphinate, and aluminum diisobutylphosphinate, but contains a structure in which diethylphosphinate, ethylisobutylphosphinate, and diisobutylphosphinate pair with the same aluminum atom.
[0018] In the examples of the present application, at the same usage amount, the flame retardant effect of pure diethylphosphinate or diisobutylphosphinate is far inferior to that of the hybrid salt containing both diethylphosphinate and ethylisobutylphosphinate. Also, the flame retardant properties are related to the content of ethylisobutylphosphinate, and only the composition in which y is within a specific range has excellent flame retardant properties, thermal properties, and excellent economic efficiency.
[0019] According to the second aspect of the present application, there is provided a method for producing the above-mentioned dialkylphosphinic acid hybrid salt, and the production method includes a step of generating reaction I in an aqueous phase for a material containing mixture A and a metal element source M to obtain the dialkylphosphinic acid hybrid salt, wherein the mixture A includes diethylphosphinic acid and / or its alkali metal salt, ethylisobutylphosphinic acid and / or its alkali metal salt, and diisobutylphosphinic acid and / or its alkali metal salt.
[0020] Optionally, the molar ratio of diethylphosphinic acid and / or its alkali metal salt, ethylisobutylphosphinic acid and / or its alkali metal salt, diisobutylphosphinic acid and / or its alkali metal salt, and the metal element source M is close to x:y:z:q, provided that q = 1 / n.
[0021] Due to the difference in M, the solubility of the hybrid salt in water is different. In the case of a hybrid salt with high solubility, since there are differences between the values of x, y, and z of diethylphosphinic acid and / or its alkali metal salt, ethylisobutylphosphinic acid and / or its alkali metal salt, diisobutylphosphinic acid and / or its alkali metal salt in the solution and the values of x, y, and z in the hybrid salt, the molar ratio with the M source also changes. Also, in order to obtain more M-containing precipitates, the molar ratio of x, y, and z of the reactants to M may exceed the theoretical calculated value.
[0022] During the actual operation, the actual values of x, y, z, and q can be determined by phosphorus nuclear magnetic resonance.
[0023] Optionally, the molar ratio of diethylphosphinic acid and / or its alkali metal salt, ethylisobutylphosphinic acid and / or its alkali metal salt, and diisobutylphosphinic acid and / or its alkali metal salt in the mixture A is the same as or substantially the same as the ratio of x, y, and z in formula (I).
[0024] Optionally, the conditions of the reaction I are a temperature of 0 to 250 °C, a pressure of 0.1 MPa to 10 MPa, and a time of 0.1 to 20 h.
[0025] Optionally, the acquisition of the mixture A includes the step of introducing ethylene and isobutene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and performing reaction II to obtain the mixture A.
[0026] Optionally, the molar ratio of phosphinic acid and / or its alkali metal salt, ethylene, and isobutene is 1:0.05 to 1.95:0.5 to 1.5.
[0027] In the actual reaction, there are side reactions such as long-chain dialkylphosphinate obtained by polymerizing ethylene, so the consumption of olefins is higher than the theoretical ratio.
[0028] Optionally, the molar ratio of the phosphinic acid and / or its alkali metal salt, ethylene, and isobutene is the same as or close to the ratio of x, y, and z in formula (I). Optionally, in the reaction II, the reaction rate depends on the ratio of x, y, and z. The larger the value of z, the slower the reaction rate. Therefore, it is necessary to control the value of z to obtain economic efficiency. Also, during the reaction of the phosphinic acid or its alkali metal salt with ethylene or isobutene, there is a maximum value of y less than 1, and after reaching this maximum value, x or z increases, so y does not reach 1. If it is necessary to make y = 1, it is necessary to separate and purify the reaction intermediate product to remove diethylphosphinic acid and / or diisobutylphosphinic acid or their salts, which has been found to be economically disadvantageous.
[0029] Specifically, in reaction II, ethylene and isobutene may be added in reverse order, added simultaneously, or partially added first.
[0030] Optionally, in reaction II, after reacting the phosphinic acid and / or its alkali metal salt with isobutene to obtain the corresponding values of y and z, ethylene is reacted substantially completely or completely. "Substantially completely" means that the total phosphorus contained in ethylphosphinate, isobutylphosphinate, and phosphinate in the reaction mixture is less than 5% mol of the total phosphorus in the reaction solution.
[0031] Specifically, after the completion of reaction I, the next reaction may be carried out directly without separating the mixture of diethylphosphinic acid, ethylisobutylphosphinic acid, diisobutylphosphinic acid, or their alkali metals.
[0032] Optionally, the mass of the water in the aqueous solution is 10 to 99% of the total mass of the radical initiator and the phosphinic acid and / or its alkali metal salt.
[0033] Specifically, if there is too little water in the aqueous solution, the solubility of the olefin in water will decrease due to the salting-out effect, resulting in a slow reaction rate. If there is too much water, the utilization rate of the reaction kettle will decrease.
[0034] Optionally, the mass of the water in the aqueous solution is 20-95% of the total mass of the radical initiator and the phosphinic acid and / or its alkali metal salt.
[0035] Optionally, the mass of the water in the aqueous solution is 45-92% of the total mass of the radical initiator and the phosphinic acid and / or its alkali metal salt.
[0036] Optionally, the mass of the water in the aqueous solution is 50-90% of the total mass of the radical initiator and the phosphinic acid and / or its alkali metal salt.
[0037] Optionally, the mass of the water in the aqueous solution is 55-90% of the total mass of the radical initiator and the phosphinic acid and / or its alkali metal salt.
[0038] Optionally, the conditions of the reaction II are a temperature of 0-250°C, a time of 0.01-50 h, and a pressure of 0-3 MPa.
[0039] Specifically, if the temperature of the reaction II is too low, the reaction rate will be slow. If the temperature is too high, the phosphinate will be easily decomposed.
[0040] Optionally, the temperature of the reaction II is 10-200°C.
[0041] Specifically, if the pressure of the reaction II is higher than 3 MPa, the pressure required for the reaction device is high and the operation is difficult.
[0042] Optionally, the pressure of the reaction II is 0.2-1.5 MPa.
[0043] Optionally, the molar ratio of the radical initiator to the phosphinic acid and / or its alkali metal salt is 0.001 to 0.1:1.
[0044] Optionally, the radical initiator is at least one selected from azo initiators, peroxide initiators, and photoinitiators. Among them, the addition amount of the radical initiator can be determined according to practical requirements.
[0045] Optionally, the azo initiator is selected from cationic and / or non-cationic azo initiators, and includes one or more of azodiisobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-amidinopropane) dichloride, and 2,2'-azodiisobutylamidine dihydrochloride.
[0046] Optionally, the peroxide initiator is preferably an inorganic peroxide and an organic peroxide radical initiator, and particularly preferably one or more of hydrogen peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, sodium percarbonate, benzoyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, and peracetic acid.
[0047] Preferably, the radical initiator is a peroxide type. Particularly preferably, the radical initiator is one selected from ammonium persulfate, potassium persulfate, and sodium persulfate.
[0048] Optionally, the molar ratio of the radical initiator to the phosphinic acid and / or its alkali metal salt is 0.003 to 0.05:1.
[0049] Optionally, the acquisition of the mixture A is Introduce isobutene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and react them. After the molar ratio of the introduced isobutene to the total phosphorus of phosphinic acid and / or its alkali metal salt becomes (y + 2z) / 1 in formula (I), stop the introduction of isobutene, continue the introduction of ethylene and react to obtain the mixture A.
[0050] Optionally, the mixture A is obtained by introducing isobutene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and after the isobutene reaction is completely or almost completely reacted, continue the introduction of ethylene and react to obtain the mixture A.
[0051] Optionally, react phosphinic acid and / or its alkali metal salt with isobutene to obtain monoisobutylphosphinic acid or its alkali metal salt equal to or approximately close to the value of y, control z to be 0.5 or less, then stop the addition of isobutene, instead add ethylene, continue the reaction in the presence of an initiator, and then react with the required metal salt to obtain a flame retardant having formula (I).
[0052] Optionally, the mixture A is obtained by introducing a part of isobutene and ethylene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator and reacting them. After the molar ratio of ethylene to the total phosphorus of phosphinic acid and / or its alkali metal salt is less than (2x + y) / 1 in formula (I) and the molar ratio of the introduced isobutene to the total phosphorus of phosphinic acid and / or its alkali metal salt becomes (y + 2z) / 1 in formula (I), stop the introduction of isobutene, continue the introduction of the remaining ethylene and react to obtain the mixture A.
[0053] Optionally, the mixture A is obtained by Introduce isobutene and a part of ethylene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and after a part of the isobutene and ethylene have completely or almost completely reacted, continue to introduce the remaining ethylene and react to obtain the mixture A, including the step of The molar ratio of the total amount of the ethylene to the isobutene is 0.33 to 39:1.
[0054] Optionally, the acquisition of the mixture A is Introduce a part of ethylene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, make the molar ratio of the part of the ethylene to the total phosphorus of the phosphinic acid and / or its alkali metal salt smaller than (2x + y) / 1 of the formula (I), and after the part of the ethylene has completely reacted, continue to introduce isobutene and react. After the molar ratio of the introduced isobutene to the total phosphorus of the phosphinic acid and / or its alkali metal salt becomes (y + 2z) / 1 of the formula (I), stop introducing isobutene, continue to introduce the remaining ethylene and react to obtain the mixture A, including the step of
[0055] Optionally, the acquisition of the mixture A is Introduce a part of ethylene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and after the part of the ethylene has completely or almost completely reacted, continue to introduce isobutene and react. After the isobutene reaction has completely or almost completely reacted, introduce the remaining ethylene and continue the reaction to obtain the mixture A, including the step of The molar ratio of the total amount of the ethylene to the isobutene is 0.33 to 39:1.
[0056] Optionally, the metal element source M is at least one selected from metal element M salts.
[0057] Optionally, the metal element M salt is at least one selected from nitrate, sulfate, hydrochloride, acetate, and oxide of metal element M.
[0058] Optionally, phosphinic acid and / or its alkali metal salt is reacted with a part of isobutene and ethylene in the presence of a radical initiator, the amounts of isobutene and ethylene are controlled, and the molar percentage of isobutylphosphinic acid or its alkali metal salt in the reaction system is close to the value of y, and the molar percentage of diisobutylphosphinic acid or its alkali metal salt is close to the value of z, and after z becomes 0.5 or less, the addition of isobutene is stopped, the remaining ethylene is added, and the reaction is continued until completion in the presence of an initiator, and then reacted with the required metal salt to obtain a dialkylphosphinic acid hybrid salt having the formula (I).
[0059] According to the third aspect of the present application, there is further provided a flame retardant containing at least one of the above dialkylphosphinic acid hybrid salts.
[0060] Optionally, the flame retardant further contains at least one selected from phosphate ions, phosphite ions, alkylphosphonate ions, and alkylphosphinate ions, and the molar content of these phosphorus-containing acid salts ions in the flame retardant is 10 mol% or less, and the number of moles of the flame retardant is converted by the number of moles of phosphorus element contained therein.
[0061] According to the fourth aspect of the present application, there is provided a flame-retardant material containing a flame retardant P and a thermoplastic polymer material, wherein the flame retardant P is used in at least one flame retardant selected from the above dialkylphosphinic acid hybrid salts and the above flame retardants.
[0062] Optionally, the content of the flame retardant P in the flame-retardant material is 1 to 35% by mass.
[0063] Optionally, the flame-retardant material contains 1 to 35 wt% of the flame retardant P and 65 to 99 wt% of the thermoplastic polymer material.
[0064] The thermoplastic polymer material in the present application refers to a plastic having heat-softening and cooling-hardening characteristics.
[0065] Specifically, the usage amount of the flame retardant P depends on the thermoplastic polymer material.
[0066] Optionally, the content of the flame retardant P in the flame-retardant material is 3 to 20 by mass % There is.
[0067] Optionally, the flame-retardant material further contains a functional additive, The functional additive is at least one selected from a reinforcing agent, a drip inhibitor, a stabilizer, a pigment, a dye, a carbonization catalyst, a dispersant, a nucleating agent, an inorganic filler, and an antioxidant.
[0068] Optionally, the reinforcing agent is selected from glass fibers.
[0069] Optionally, the drip inhibitor is selected from Teflon.
[0070] Optionally, the inorganic filler is at least one selected from mica, calcium carbonate, calcium oxide, and silica.
[0071] Optionally, the content of the functional additive in the flame-retardant material is 5 to 40% by mass.
[0072] Optionally, the flame-retardant material further contains a flame retardant Q, The flame retardant Q is at least one selected from a nitrogen-based flame retardant and a boron-based flame retardant.
[0073] Optionally, the nitrogen-based flame retardant is at least one selected from melamine cyanurate, melamine polyphosphate, and ammonium polyphosphate. The boron-based flame retardant is selected from zinc borate.
[0074] Optionally, the content of the flame retardant Q in the flame-retardant material is 0.5 to 20% by mass.
[0075] Optionally, the thermoplastic polymer material is at least one selected from polyamide and polyester.
[0076] Optionally, the polyamide is at least one selected from aliphatic polyamides, aromatic polyamides, semi-aromatic polyamides, and copolymers of semi-aromatic polyamides and aliphatic polyamides.
[0077] Those skilled in the art can add other flame retardants B, such as nitrogen-based flame retardants containing melamine cyanurate, phosphorus-nitrogen-based flame retardants containing melamine polyphosphate or ammonium polyphosphate, and boron-based flame retardants containing zinc borate, to the flame-retardant material according to specific requirements.
[0078] Optionally, the flame-retardant material contains 5-40% by mass of reinforced glass fibers. Other auxiliaries include, for example, stabilizers, anti-dripping agents, pigments, dyes, carbonization catalysts, dispersants, flame retardants, nucleating agents, and inorganic fillers or mixtures thereof. The inorganic fillers are, for example, mica, calcium carbonate, calcium oxide, and silica. The total of all components is 100% by mass.
[0079] According to the common general knowledge in the art, polyamide is also called polyamide fiber or nylon, and is a general term for polymers having -NH-C(O)-amide in its structural units. It is synthesized by the condensation or ring-opening reaction of one or more dicarboxylic acids and one or more diamines, and / or one or more amino acids, and / or one or more lactams. Polyamides are generally classified into aliphatic polyamides, aromatic polyamides, and semi-aromatic polyamides according to the components of the main chain. Semi-aromatic polyamides refer to those having an aromatic group in at least one monomer structure in their synthetic monomers.
[0080] Optionally, the aliphatic polyamide is any one or more mixtures selected from copolymers of polyamide 6 and polyamide 66, polyamide 6, and polyamide 66.
[0081] Optionally, the semi-aromatic polyamide can be produced from any one or more aromatic dicarboxylic acids and any one or more aliphatic diamines, or from any one or more aromatic diamines and any one or more aliphatic dicarboxylic acids. Further, one or any plurality selected from dicarboxylic acids, diamines, lactams and amino acids can be added to the system to produce a polyamide copolymer with corresponding properties. The added dicarboxylic acid is an aromatic dicarboxylic acid and / or an aliphatic dicarboxylic acid. The added diamine is an aromatic diamine and / or an aliphatic diamine. The added lactam may be an aliphatic lactam or an aromatic lactam. The added amino acid may be an aromatic amino acid or an aliphatic amino acid.
[0082] Optionally, the semi-aromatic polyamide is produced from any one or more aromatic dicarboxylic acids selected from terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid and one or more aliphatic diamines selected from butylenediamine, hexamethylenediamine, octamethylenediamine, decamethylenediamine, and 2-methylpentamethylenediamine.
[0083] Optionally, the semi-aromatic polyamide is produced from an aliphatic diamine, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid.
[0084] Optionally, the semi-aromatic polyamide is produced from an aliphatic diamine and an aromatic dicarboxylic acid, and optionally, an aliphatic dicarboxylic acid may be added, and the molar percentage of the aliphatic dicarboxylic acid is 0 to 45% of the total dicarboxylic acids, that is, the number of moles of the aliphatic dicarboxylic acid / (the number of moles of the aliphatic dicarboxylic acid + the number of moles of the aromatic dicarboxylic acid) = 0 to 45%.
[0085] Optionally, the aromatic dicarboxylic acid is any one or more selected from terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid, the aliphatic diamine is any one or more selected from butylenediamine, hexamethylenediamine, octamethylenediamine, decamethylenediamine, and 2-methylpentamethylenediamine, and the aliphatic dicarboxylic acid is one or more selected from adipic acid, succinic acid, sebacic acid, and octanoic acid.
[0086] Optionally, the polyamide is any one or more selected from poly(hexamethylene terephthalate) (abbreviated as PA6T), polyhexamethylene isophthalamide (abbreviated as PA6I), terephthalic acid / hexamethylenediamine / caprolactam copolymer (abbreviated as PA6T / 6), terephthalic acid / hexamethylenediamine / adipic acid copolymer (abbreviated as PA6T / 66), terephthalic acid / hexamethylenediamine / adipic acid / isophthalic acid copolymer (abbreviated as PA6T / 6I / 66), polynonamethylene terephthalamide (abbreviated as PA9T), polydecamethylene terephthalamide (abbreviated as PA10T), poly(dodecamethylene terephthalamide) (abbreviated as PA12T), terephthalic acid / hexamethylenediamine / laurolactam copolymer (abbreviated as PA6T / 12), polymetaxylylene adipamide (abbreviated as MXD6), terephthalic acid / hexamethylenediamine / 2-methylpentamethylenediamine copolymer (abbreviated as PA6T / 2-MPMDT), and terephthalic acid / 2,2,4-trimethylhexamethylenediamine / 2,4,4-trimethylhexamethylenediamine copolymer.
[0087] Optionally, the aliphatic polyamide is at least one selected from polyamide 6, polyamide 66, and a copolymer of polyamide 6 and polyamide 66.
[0088] Optionally, the semi-aromatic polyamide is selected from polyphthalamide (PPA).
[0089] Optionally, the polyester is selected from polybutylene terephthalate (PBT).
[0090] In the examples of the present application, without considering the amounts of other phosphorus-containing impurities, the values of x, y, and z in formula (I) satisfy x + y + z = 1 and x + z > 0. The flame retardant having the composition of formula (I) may contain trace amounts of other phosphorus-containing ions. Due to impurities in the raw materials or the generation of impurities during the synthesis process, some trace amounts of phosphate ions, phosphite ions, alkylphosphonate ions, and alkylphosphinate ions may be present in the flame retardant. Oligomer products obtained by polymerizing ethylene, such as ethyl n-butylphosphinate ions, ethylhexylphosphinate ions, butylbutylphosphinate ions, and butylhexylphosphinate ions, may also be present as impurities in the flame retardant having the composition of formula (I). However, as long as the total amount of these other phosphorus-containing acid salt ions does not exceed 10% mol of the total phosphorus, it does not affect the normal operation of the flame retardant having the composition of formula (I).
[0091] In the examples of the present application, the ratio of x, y, and z in formula (I) can be determined by 31 P-NMR (nuclear magnetic) after alkali decomposition or acid decomposition of the flame retardant. Diethylphosphinate, ethylisobutylphosphinate, and diisobutylphosphinate have different 31 chemical shifts of P and 31 show three independent peaks in the P-NMR spectrum. The peak areas of these three peaks correspond to the molar concentrations of the three phosphinates respectively. Therefore, the values of x, y, and z can be easily calculated from the ratio of the peak areas. [[Effect of the Invention]]
[0092] The beneficial effects that the present application can achieve are as follows.
[0093] (1) The dialkylphosphinic acid hybrid salt having the composition of formula (I) according to the present invention has a small addition amount, high flame retardancy efficiency for various polymer materials, and excellent economic efficiency. It not only overcomes the drawback of the diethylphosphinate having low flame retardancy efficiency for polymer materials, but also overcomes the drawbacks of the diisobutylphosphinate having too high volatility and low flame retardancy efficiency for polyester, and can be widely applied to the flame retardancy of various polymer materials that require high-temperature processing.
[0094] (2) In the method for producing the dialkylphosphinic acid hybrid salt according to the present invention, the drawback of having to independently produce dialkylphosphinic acid is avoided, and since water is used as the reaction solvent, it is excellent in environmental protection. The raw materials are easily available and the economic efficiency is high.
Brief Description of the Drawings
[0095]
Figure 1
Figure 2
Figure 3
Modes for Carrying Out the Invention
[0096] Hereinafter, the present invention will be described in more detail in combination with examples, but the present invention is not limited to these examples.
[0097] Unless otherwise specified, all raw materials in the examples of this application are commercially available.
[0098] The raw materials used in the examples are as follows.
[0099] PA66 (also called polyamide 66 or nylon 66): Zytel 70G35 HSL NC010 from DuPont, USA, with a glass fiber content of 35% by mass.
[0100] PA6 (also called polyamide 6 or nylon 6): Zytel 73G30L NC010 from DuPont, USA, with a glass fiber content of 30% by mass.
[0101] PPA (high-temperature nylon): HTN 51G35 HSL NC010 from DuPont, USA, with a glass fiber content of 35% by mass.
[0102] PBT (polybutylene terephthalate): Crastin SK605 NC010 from DuPont, USA, with a glass fiber content of 30% by mass.
[0103] ADP: Aluminum diethylphosphinate, Exolit OP1230 from Clariant, Germany.
[0104] ABP: Aluminum diisobutylphosphinate manufactured according to US Patent 7807737.
[0105] MPP: Melamine polyphosphate, Suzhou Kaima Chemical Technology Co., Ltd.
[0106] Antioxidant 1010: Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], from Shanghai MACKLIN.
[0107] Antioxidant 168: Tris(2,4-di-tert-butylphenyl)phosphite, from Strem, USA.
[0108] Composite antioxidant: A mixture of antioxidant 1010 (pentaerythritol tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) and antioxidant 168 (tris(2,4-di-tert-butylphenyl) phosphite) in a mass ratio of 1:1.
[0109] Combustion test standard: GB / T 2408-2008 standard.
[0110] Nuclear magnetic resonance (NMR) test: The model number of the equipment used is AVANCE III 400MHz, manufactured by Bruker, Germany.
[0111] Nuclear magnetic resonance phosphorus spectrum ( 31 P-NMR) test method: The chemical shift of 85% phosphoric acid is 0, the pre-delay is D1 = 10 seconds, scanned 32 times, and the ratio of the peak areas is taken as the molar ratio of diethylphosphate ions, ethylisobutylphosphate ions, and diisobutylphosphate ions.
[0112] X-ray diffraction (XRD) test: The model number of the equipment used is D8 ADVANCED AVINCI, manufactured by Bruker, Germany.
[0113] TGA thermogravimetric reduction treatment: The model number of the equipment used is Q500, manufactured by TA Instruments, USA.
[0114] [Example 1 Preparation of a hybrid salt having the composition of formula (I), where x = 0.87, y = 0.13, z = 0, M = Al, n = 3] Dissolve 100 grams of sodium phosphinate monohydrate in 500 grams of water, put it into a 1L stainless steel autoclave, replace the autoclave with nitrogen gas twice, perform vacuum suction, and then fill it with isobutene until the pressure stops rising. Heat the reaction solution to about 90 °C. At this time, the pressure gauge shows 0.3 MPa. Next, inject an aqueous sodium persulfate solution with a concentration of 4% by mass at a constant rate of 10 ml / h, continuously introduce isobutene into the autoclave, and measure the introduction amount of olefin with a gas flow meter. After 0.3 hours, stop the introduction of isobutene, start the introduction of ethylene, and raise the pressure to 0.8 MPa. After 9.0 hours, stop the introduction of ethylene, but continue to add the initiator. After half an hour, since the pressure in the autoclave no longer drops, it indicates that the reaction is complete. Cool down and release the pressure, and purge with N 2 to obtain a colorless and transparent reaction solution by discharging it.
[0115] Sampling was carried out during the reaction, and nuclear magnetic analysis was performed. 31 The P-NMR results are shown in Table 1.
[0116]
Table 1
[0117] 690 grams of a portion of the above solution was slowly added to an aqueous solution with a concentration of 20% by mass containing 89.97 grams of aluminum sulfate octadecahydrate. The reaction temperature was controlled at 70 °C, and the pH value was adjusted to 3.0 or less to obtain a large amount of precipitate. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.5. Then, the filter cake was dried at 120 °C to obtain 106.75 grams, and the yield was 92.9%. The sample was dissolved in an aqueous solution of sodium hydroxide and subjected to phosphorus nuclear magnetic analysis. As a result, diethylphosphinate was 85.79%, ethylisobutylphosphinate was 12.36%, diisobutylphosphinate was 0.45%, and the rest were long-chain alkylphosphinates, ethylphosphonates, and phosphite impurities. After normalization, x = 0.87, y = 0.13, and z = 0.
[0118] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second-highest characteristic peak measured by XRD were 9.787 Å (100%) and 10.039 Å (66.1%) respectively, and the results are shown in Table 2.
[0119]
Table 2
[0120] [Example 2a Preparation of a hybrid salt having the composition of formula (I), where x = 0.83, y = 0.16, z = 0.01, M = Al, n = 3] Dissolve 100 g of sodium phosphinate monohydrate in 500 g of water, put it into a 1 L stainless steel autoclave, replace the autoclave with nitrogen gas twice, perform vacuum suction, and then fill it with isobutene until the pressure no longer rises. Heat the reaction solution to about 90 °C. At this time, the pressure gauge shows 0.3 MPa. Next, inject an aqueous sodium persulfate solution with a concentration of 4% by mass at a constant rate of 10 ml / h, continuously introduce isobutene into the autoclave, and measure the introduction amount of olefin with a gas flow meter. After 1.0 h, stop the introduction of isobutene, start the introduction of ethylene, and raise the pressure to 0.8 MPa. After 9.0 h, stop the introduction of ethylene, but continue to add the initiator. After half an hour, since the autoclave pressure no longer drops, it indicates that the reaction is complete. Cool down the temperature and release the pressure, and purge with N 2 to obtain a colorless and transparent reaction solution by discharging.
[0121] Collect the reaction solution and perform nuclear magnetic measurement. 31 The P-NMR results are shown in Table 3.
[0122]
Table 3
[0123] Slowly add 766 g of a part of the above solution to an aqueous solution with a concentration of 20% by mass containing 89.97 g of aluminum sulfate octadecahydrate, control the reaction temperature at 70 °C, adjust the pH value to 3.0 or less, and obtain a large amount of precipitate. After 1 h, the dropping is completed. Filter while it is hot, and wash the filter cake with clean water until the pH > 4.5. Then, dry the filter cake at 120 °C to obtain 95.2 g of a white powdery product, and the yield is 90.7%.
[0124] The sample was dissolved in an aqueous solution of sodium hydroxide and subjected to phosphorus nuclear magnetic analysis. As a result, diethyl phosphinate was 80.35%, ethyl isobutyl phosphinate was 16.05%, diisobutyl phosphinate was 0.70%, and the rest were long-chain alkyl phosphinates, ethyl phosphonates, and phosphite impurities. After normalization, x = 0.83, y = 0.16, and z = 0.01.
[0125] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second-highest characteristic peak measured by XRD were 9.812 Å (100%) and 10.237 Å (86.7%), respectively, and the results are shown in Table 4.
[0126]
Table 4
[0127] [Production of a hybrid salt having the composition of formula (I) in Example 2b, where x = 0.83, y = 0.16, z = 0.01, M = Cu, and n = 2] According to the method of Example 2a, copper sulfate was used instead of aluminum sulfate to obtain a copper hybrid salt with x = 0.83, y = 0.16, and z = 0.01. The XRD results of the XRD test on the sample are shown in Table 5.
[0128]
Table 5
[0129] [Production of a hybrid salt having the composition of formula (I) in Example 3, where x = 0.70, y = 0.29, z = 0.01, M = Al, and n = 3] Dissolve 100 grams of sodium phosphinate monohydrate in 500 grams of water, put it into a 1L stainless steel autoclave, replace the autoclave with nitrogen gas twice, perform vacuum suction, and then fill it with isobutene until the pressure no longer rises. Heat the reaction solution to about 90 °C. At this time, the pressure gauge shows 0.3 MPa. Next, inject an aqueous solution of sodium persulfate with a concentration of 3.0% by mass at a constant rate of 10 ml / h, continuously introduce isobutene into the autoclave, and measure the introduction amount of olefin with a gas flow meter. After 1.5 hours, stop the introduction of isobutene, start the introduction of ethylene, and raise the pressure to 0.8 MPa. After 10.5 hours, stop the introduction of ethylene, but continue to add the initiator. After half an hour, since the pressure in the autoclave no longer decreased, it indicated that the reaction was completed. Cool down the temperature and release the pressure, and purge with N 2 and discharge to obtain a colorless and transparent reaction solution.
[0130] Sampling was carried out during the reaction, and the results of nuclear magnetic measurement are shown in Table 6.
[0131]
Table 6
[0132] Slowly add 724 grams of the above solution to an aqueous solution with a concentration of 20% by mass containing 104.79 grams of aluminum sulfate octadecahydrate, control the reaction temperature at 70 °C, adjust the pH value to 3.0 or less, and obtain a large amount of precipitate. After 1 hour, the dropping was completed. Filter while it is hot, and wash the filter cake with clean water until the pH > 4.5. Then, dry the filter cake at 120 °C to obtain 117.5 grams, and the yield was 90.2%.
[0133] The sample was dissolved in an aqueous solution of sodium hydroxide, and the results of phosphorus nuclear magnetic analysis showed that diethyl phosphate was 69.15%, ethyl isobutyl phosphate was 28.57%, diisobutyl phosphate was 1.12%, and the rest were long-chain alkyl phosphate impurities. After normalization, x = 0.70, y = 0.29, and z = 0.01.
[0134] As a result of performing XRD tests on the samples, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 10.407 Å (100%) and 9.902 Å (47.4%), respectively, and the results are shown in Table 7.
[0135]
Table 7
[0136] The hybrid salt obtained in this example was alkali-decomposed, 31 The 31P-NMR (nuclear magnetic) spectrum is shown in Figure 3. Since the peak areas of these three peaks correspond to the molar concentrations of the three phosphates, the values of x, y, and z could be easily calculated from the ratio of the peak areas.
[0137] [Example 4a Preparation of a hybrid salt having the composition of formula (I), where x = 0.60, y = 0.38, z = 0.02, M = Al, n = 3] 100 grams of sodium phosphinate monohydrate was dissolved in 500 grams of water, charged into a 1 L stainless steel autoclave, the autoclave was replaced with nitrogen gas twice, vacuum-sucked, and then filled with isobutene until the pressure no longer increased. The reaction solution was heated to about 90 °C. At this time, the pressure gauge showed 0.3 MPa. Next, an aqueous sodium persulfate solution with a concentration of 3.0% by mass was injected at a constant rate of 10 ml / h, isobutene was continuously introduced into the autoclave, and the introduction amount of olefin was measured by a gas flow meter. After 2.0 hours, the introduction of isobutene was stopped, the introduction of ethylene was started, and the pressure was raised to 0.8 MPa. After 15.5 hours, the introduction of ethylene was stopped, but the addition of the initiator was continued. After half an hour, since the autoclave pressure no longer decreased, it indicated that the reaction was completed. The temperature was lowered and the pressure was released, and purged with N 2 to obtain a colorless and transparent reaction solution.
[0138] Sampling was carried out during the reaction, and the results of the nuclear magnetic measurements are shown in Table 8.
[0139]
Table 8
[0140] 847 grams of the above solution was slowly added to an aqueous solution with a concentration of 20% by mass containing 104.79 grams of aluminum sulfate octadecahydrate. The reaction temperature was controlled at 70 °C, and the pH value was adjusted to 3.0 or less to obtain a large amount of precipitate. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.5. Then, the filter cake was dried at 120 °C to obtain 126.1 grams, and the yield was 94.9%.
[0141] The sample was dissolved in an aqueous solution of sodium hydroxide, and as a result of performing phosphorus nuclear magnetic analysis, diethyl phosphate was 60.29%, ethyl isobutyl phosphate was 38.24%, and diisobutyl phosphate was 1.47%, that is, x = 0.60, y = 0.38, z = 0.02.
[0142] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 10.455 Å (100%) and 4.436 Å (14.2%) respectively, and the results are shown in Table 9.
[0143]
Table 9
[0144] [Example 4b Preparation of a hybrid salt having the composition of formula (I), where x = 0.63, y = 0.36, z = 0.01, M = Fe, n = 3] According to Example 4a, 49.46 grams of the reaction solution was slowly added to a 15% aqueous solution containing 5.41 g of ferric chloride hexahydrate. The reaction temperature was controlled at 70 °C, and the pH value was adjusted to 2.0 or less to obtain a large amount of precipitate. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.0. Then, the filter cake was dried at 120 °C to obtain 8.40 grams, and the yield was 93.7%.
[0145] The sample was dissolved in an aqueous solution of sodium hydroxide and subjected to phosphorus nuclear magnetic analysis. As a result, the content of diethyl phosphinate was 63.26%, ethyl isobutyl phosphinate was 35.82%, and diisobutyl phosphinate was 0.92%, that is, x = 0.63, y = 0.36, and z = 0.01.
[0146] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 10.407 Å (100%) and 4.502 Å (8.0%), respectively. The results are shown in Table 10.
[0147] [Table 10]
[0148] [Example 4c Preparation of a hybrid salt having the composition of formula (I), wherein x = 0.62, y = 0.37, z = 0.01, M = Zn, and n = 2] According to Example 4a, 197.85 grams of the reaction solution was slowly added to a 15% aqueous solution containing 34.51 grams of zinc sulfate heptahydrate. The reaction temperature was controlled at 70 °C. After the addition was completed, it was cooled and dried to obtain a white solid. The sample was dissolved in an aqueous solution of sodium hydroxide and subjected to phosphorus nuclear magnetic analysis. As a result, the content of diethyl phosphinate was 62.0%, ethyl isobutyl phosphinate was 36.7%, and diisobutyl phosphinate was 1.3%, that is, x = 0.62, y = 0.37, and z = 0.01.
[0149] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 8.741 Å (100%) and 9.044 Å (57.6%), respectively. The results are shown in Table 11.
[0150] [Table 11]
[0151] [Example 5a Preparation of a hybrid salt having the composition of formula (I), where x = 0.45, y = 0.52, z = 0.03, M = Al, and n = 3] 100 grams of sodium phosphinate monohydrate was dissolved in 500 grams of water and charged into a 1 L stainless steel autoclave. The autoclave was purged twice with nitrogen gas and then evacuated. After that, isobutene was filled until the pressure no longer increased. The reaction solution was heated to about 90 °C. At this time, the pressure gauge showed 0.3 MPa. Next, an aqueous sodium persulfate solution with a concentration of 3.0% by mass was injected at a constant rate of 10 ml / h, and isobutene was continuously introduced into the autoclave. After 5.5 hours, the introduction of isobutene was stopped, and the introduction of ethylene was started, and the pressure was increased to 0.8 MPa. After 17 hours, when the reaction was complete, the introduction of ethylene was stopped, the temperature was decreased, and the pressure was released. It was purged with N 2 and discharged to obtain a colorless and transparent reaction solution.
[0152] Sampling was carried out during the reaction, and the results of nuclear magnetic resonance are shown in Table 12.
[0153]
Table 12
[0154] 445 grams of the above solution was slowly added to a 10% aqueous solution containing 59.98 grams of aluminum sulfate octadecahydrate. The reaction temperature was controlled at 70 °C, and the pH value was adjusted to 2.9 or less to obtain a large amount of precipitate. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with hot water until the pH > 4.5. Then, the filter cake was dried at 120 °C to obtain 69.3 grams, and the yield was 89%.
[0155] The sample was dissolved in an aqueous solution of sodium hydroxide, and phosphorus nuclear magnetic analysis was performed. As a result, diethyl phosphinate was 44.18%, ethyl isobutyl phosphinate was 50.45%, diisobutyl phosphinate was 3.24%, and the rest were long-chain alkyl phosphinate and ethyl phosphonate impurities. After normalization, x = 0.45, y = 0.52, and z = 0.03.
[0156] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second-highest characteristic peak measured by XRD were 10.626 Å (100%) and 4.436 Å (12.7%), respectively, and the results are shown in Table 13.
[0157] [Table 13]
[0158] [Example 5b Preparation of a hybrid salt having the composition of formula (I), where x = 0.48, y = 0.49, z = 0.03, M = Fe, and n = 3] According to Example 5a, 51.3 grams of the reaction solution was slowly added to a 15% aqueous solution containing 5.41 grams of ferric chloride hexahydrate, the reaction temperature was controlled at 70 °C, the pH value was adjusted to 2.0 or less, and a large amount of precipitate was obtained. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.0. Then, the filter cake was dried at 120 °C to obtain 8.70 grams, and the yield was 94.7%.
[0159] The sample was dissolved in an aqueous solution of sodium hydroxide, and phosphorus nuclear magnetic analysis was performed. As a result, diethyl phosphinate was 47.22%, ethyl isobutyl phosphinate was 48.25%, diisobutyl phosphinate was 2.13%, and the rest were long-chain alkyl phosphinate and ethyl phosphonate impurities. After normalization, x = 0.48, y = 0.49, and z = 0.03.
[0160] As a result of performing XRD tests on the samples, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 10.603 Å (100%) and 4.524 Å (11.2%) respectively, and the results are shown in Table 14.
[0161]
Table 14
[0162] [Example 6 Preparation of a hybrid salt having the composition of formula (I), where x = 0.31, y = 0.64, z = 0.05, M = Al, n = 3] 100 grams of sodium phosphinate monohydrate was dissolved in 500 grams of water, charged into a 1 L stainless steel autoclave, the autoclave was purged with nitrogen gas twice, vacuum suctioned, and then filled with isobutene until the pressure no longer increased. The reaction solution was heated to about 90 °C. At this time, the pressure gauge showed 0.3 MPa. Next, an aqueous solution of 4.0% 2,2’-azobis(2-amidinopropane) dichloride was injected at a constant rate of 10 ml / h, and isobutene was continuously introduced into the autoclave. After 9.5 hours, the introduction of isobutene was stopped, the introduction of ethylene was started, and the pressure was raised to 0.8 MPa. After 20 hours, the reaction was complete, the introduction of ethylene was stopped, the temperature was lowered, the pressure was released, and it was purged with N 2 to obtain a colorless and transparent reaction solution.
[0163] Sampling was carried out during the reaction, and the results of nuclear magnetic measurements are shown in Table 15.
[0164]
Table 15
[0165] 512 grams of the above solution was slowly added to a 10% aqueous solution containing 59.98 grams of aluminum sulfate octadecahydrate, the reaction temperature was controlled at 70 °C, the pH value was adjusted to 2.9 or less, and a large amount of precipitate was obtained. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.5. Then, the filter cake was dried at 120 °C to obtain 74.46 grams, and the yield was 93.7%.
[0166] The sample was dissolved in an aqueous solution of sodium hydroxide and subjected to phosphorus nuclear magnetic analysis. As a result, diethyl phosphinate was 30.76%, ethyl isobutyl phosphinate was 63.27%, diisobutyl phosphinate was 4.60%, and the rest were long-chain alkyl phosphinates and ethyl phosphonate impurities. After normalization, x = 0.31, y = 0.64, and z = 0.05.
[0167] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second-highest characteristic peak measured by XRD were 10.965 Å (100%) and 4.463 Å (9.9%), respectively, and the results are shown in Table 16.
[0168]
Table 16
[0169] [Example 7 Preparation of a Hybrid Salt Having the Composition of Formula (I), where x = 0.28, y = 0.68, z = 0.04, M = Al, and n = 3] Dissolve 100 grams of sodium phosphinate monohydrate in 500 grams of water, put it into a 1L stainless steel autoclave, replace the autoclave with nitrogen gas twice, perform vacuum suction, and then fill it with isobutene until the pressure stops rising. Heat the reaction solution to about 90 °C. At this time, the pressure gauge shows 0.3 MPa. Next, inject an aqueous solution of sodium persulfate with a concentration of 3.0% by mass at a constant rate of 10 ml / h, and continuously introduce isobutene into the autoclave. After 10.5 hours, stop the introduction of isobutene, start the introduction of ethylene, and raise the pressure to 0.8 MPa. After 21 hours, the reaction basically ends, stop the introduction of ethylene, cool down the temperature, release the pressure, and purge with N 2 to obtain a colorless and transparent reaction solution by discharging.
[0170] Sampling was carried out during the reaction, and the results of nuclear magnetic resonance are shown in Table 17.
[0171]
Table 17
[0172] For the above solution, first oxidize the mono-added product with sufficient 30% hydrogen peroxide solution, and then slowly add it to a 10% aqueous solution containing 104.79 grams of aluminum sulfate octadecahydrate, control the reaction temperature at 70 °C, adjust the pH value to below 2.9, and obtain a large amount of precipitate. After 1 hour, the dropping is completed. Filter while it is hot, and wash the filter cake with clean water until the pH > 4.5. Then, dry the filter cake at 120 °C to obtain 124.99 grams, and the yield is 91.7%.
[0173] The sample was dissolved in an aqueous solution of sodium hydroxide, and phosphorus nuclear magnetic resonance analysis was performed. As a result, diethyl phosphinate was 27.78%, ethyl isobutyl phosphinate was 66.83%, diisobutyl phosphinate was 4.00%, and the rest were other phosphorus-containing impurities. After normalization, x = 0.28, y = 0.68, and z = 0.04.
[0174] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 10.913 Å (100%) and 4.461 Å (12.6%), respectively, and the results are shown in Table 18.
[0175]
Table 18
[0176] [Example 8 Production of a hybrid salt having the composition of formula (I), where x = 0.03, y = 0.58, z = 0.39, M = Al, n = 3] 100 grams of sodium phosphinate monohydrate was dissolved in 500 grams of water, charged into a 1 L stainless steel autoclave, the autoclave was replaced with nitrogen gas twice, vacuum suctioned, and then filled with isobutene until the pressure no longer increased. The reaction solution was heated to about 90 °C. At this time, the pressure gauge showed 0.3 MPa. Next, an aqueous sodium persulfate solution with a concentration of 3.0 mass% was injected at a constant rate of 10 ml / h, and isobutene was continuously introduced into the autoclave. After 13 hours, the introduction of isobutene was stopped, the introduction of ethylene was started, and the pressure was increased to 0.8 MPa. After 25 hours, the introduction of ethylene was stopped, the temperature was lowered, the pressure was released, and purged with N 2 to obtain a colorless and transparent reaction solution by discharging.
[0177] For the above solution, first, the mono-added product was oxidized with sufficient 30% hydrogen peroxide solution. Next, 500 grams of the solution was slowly added to a 10% aqueous solution containing 13.33 grams of aluminum sulfate octadecahydrate. The reaction temperature was controlled at 70 °C, the pH value was adjusted to 2.9 or less, and a large amount of precipitate was obtained. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.5. Then, the filter cake was dried at 120 °C to obtain 19.05 grams, and the yield was 94%.
[0178] The sample was dissolved in an aqueous solution of sodium hydroxide, and phosphorus nuclear magnetic analysis was performed. As a result, the content of diethyl phosphinate was 2.69%, ethyl isobutyl phosphinate was 52.89%, and diisobutyl phosphinate was 35.84%. After normalization, x = 0.03, y = 0.58, and z = 0.39.
[0179] As a result of performing an XRD test on the sample, the corresponding interlayer spacings of the characteristic peak with the highest relative intensity and the second highest characteristic peak measured by XRD were 11.619 Å (100%) and 4.492 Å (11.7%), respectively. The results are shown in Table 19.
[0180] [Table 19]
[0181] [Example 9 Production of a hybrid salt having the composition of formula (I), where x = 0.03, y = 0.52, z = 0.45, M = Al, and n = 3] 100 grams of sodium phosphinate monohydrate was dissolved in 500 grams of water and charged into a 1 L stainless steel autoclave. The reaction kettle was replaced with nitrogen gas twice, vacuum suctioned, and then filled with isobutene until the pressure no longer increased. The reaction solution was heated to about 90 °C. At this time, the pressure gauge showed 0.3 MPa. Next, an aqueous solution of sodium persulfate with a concentration of 3.0% by mass was injected at a constant rate of 10 ml / h, and isobutene was continuously introduced into the reaction kettle. After 15 hours, the introduction of isobutene was stopped, the introduction of ethylene was started, and the pressure was increased to 0.8 MPa. After 27 hours, the reaction was complete, the introduction of ethylene was stopped, the temperature was lowered, the pressure was released, and purged with N 2 to obtain a colorless and transparent reaction solution.
[0182] Sampling was carried out during the reaction, and the results of nuclear magnetic measurement are shown in Table 20.
[0183] [Table 20]
[0184] 280 g of the above solution was slowly added to a 10% aqueous solution containing 7.46 g of aluminum sulfate octadecahydrate, the reaction temperature was controlled at 70 °C, the pH value was adjusted to 2.9 or less, and a large amount of precipitate was obtained. After 1 hour, the dropping was completed. It was filtered while it was hot, and the filter cake was washed with clean water until the pH > 4.5. Then, the filter cake was dried at 120 °C to obtain 10.7 g, and the yield was 94.3%.
[0185] The sample was dissolved in an aqueous solution of sodium hydroxide, and as a result of performing phosphorus nuclear magnetic analysis, the content of diethylphosphinate was 2.9%, the content of ethylisobutylphosphinate was 51.0%, and the content of diisobutylphosphinate was 43.5%. After normalization, x = 0.03, y = 0.52, and z = 0.45.
[0186] An XRD test was performed on the dried sample. The X-ray diffraction (XRD) results are shown in Table 21 below. As can be seen from the characteristic peak with the highest relative intensity in Table 21, the interlayer spacing was mainly 11.666 Å.
[0187]
Table 21
[0188] The results of performing a TGA test on the dialkylphosphinic acid hybrid salts obtained in Example 1, Example 2a, Example 4a, Example 7, Example 8, and Example 9 are shown in FIG. 1. FIG. 1 is a thermogravimetric reduction curve diagram (TGA) of hybrid salts, aluminum diethylphosphinate (ADP), and aluminum diisobutylphosphinate (ABP) having different x, y, and z values. As can be seen from the figure, the thermogravimetric reduction of aluminum diisobutylphosphinate was the fastest and its thermal stability was the lowest. The larger the z value, the faster the thermogravimetric reduction of the hybrid salt.
[0189] [Example 10 (Comparative Example) Iron Diethylphosphinate] 93.82 g of an aqueous solution of sodium diethylphosphinate (containing 2.1 mol% of sodium ethylbutylphosphinate and 0.5 mol% of sodium ethylphosphonate) with 18.4% by mass was slowly added over half an hour to a 15% by mass aqueous solution containing 10.81 g of ferric chloride hexahydrate while maintaining a reaction temperature of 70 °C and pH = 2, and then kept warm for half an hour. It was filtered while it was hot, and the filter cake was washed with clean water until pH > 4. Thereafter, the filter cake was dried at 120 °C to obtain 15.5 g, and the yield was 92.5%.
[0190] The results of performing XRD tests on the samples are shown in Table 22.
[0191] [Table 22]
[0192] [Example 11] Polyamide PA66, the hybrid salt produced in Example 1, and a composite antioxidant were mixed in a mass ratio of 79.6:20:0.4 in an internal mixer set at a temperature of 280 °C and a rotation speed of 50 revolutions per minute, taken out after 5 minutes, cooled, and dried. Next, it was filled into a mold, preheated with a press vulcanizer at 280 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-1.
[0193] [Example 12] Polyamide PA6, the hybrid salt produced in Example 1, and a composite antioxidant were mixed in a mass ratio of 79.6:20:0.4 in an internal mixer set at a temperature of 260 °C and a rotation speed of 50 revolutions per minute, taken out after 5 minutes, cooled, and dried. Next, it was filled into a mold, preheated with a press vulcanizer at 260 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-1.
[0194] [Example 13] Polyester PBT, the hybrid salt produced in Example 1, and the composite antioxidant were mixed at a mass ratio of 84.6:15:0.4 in an internal mixer at a set temperature of 260 °C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 260 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-0.
[0195] [Examples 14 - 40] For the flame retardants of Examples 2 - 9, samples were produced and tested according to the methods of Examples 11 - 13 in polyamide PA66, PA6, PPA, and PBT respectively. The results are shown in Tables 23 and 24.
[0196] [Example 41] Polyamide PA66, the hybrid salt produced in Example 8, MPP, and the composite antioxidant were mixed at a mass ratio of 82.6:12:5:0.4 in an internal mixer at a set temperature of 280 °C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 280 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-0.
[0197] [Comparative Example 1] Polyamide PA66, iron diethylphosphinate produced in Example 10, and the composite antioxidant were mixed at a mass ratio of 79.6:20:0.4 in an internal mixer at a set temperature of 280 °C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 280 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample had no UL94 grade.
[0198] [Comparative Example 2] Polyamide PA66, ADP, and a composite antioxidant were mixed in a mass ratio of 79.6:20:0.4 in an internal mixer at a set temperature of 280°C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 280°C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold-pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 no grade.
[0199] [Comparative Example 3] Polyamide PA6, ADP, and a composite antioxidant were mixed in a mass ratio of 79.6:20:0.4 in an internal mixer at a set temperature of 260°C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 260°C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold-pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL-94 no grade.
[0200] [Comparative Example 4] Polyester PBT, ADP, and a composite antioxidant were mixed in a mass ratio of 84.6:15:0.4 in an internal mixer at a set temperature of 260°C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 260°C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold-pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-2.
[0201] [Comparative Example 5] Polyester PBT, aluminum diisobutylphosphinate (ABP), and a compound antioxidant were mixed in a mass ratio of 84.6:15:0.4 in an internal mixer at a set temperature of 260 °C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 260 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold-pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-2.
[0202] [Comparative Example 6] Polyamide PA66, aluminum diisobutylphosphinate (ABP), and a compound antioxidant were mixed in a mass ratio of 87.1:12.5:0.4 in an internal mixer at a set temperature of 280 °C and a rotation speed of 50 revolutions per minute. After 5 minutes, it was taken out, cooled, and dried. Next, it was filled into a mold, preheated in a press vulcanizer at 280 °C for 10 minutes, maintained at 10 MPa for 5 minutes, and then cold-pressed. After cooling, samples were cut out and tested. The flame retardancy grade of the 1.6 mm sample was UL94 V-1.
[0203] The results of the comparative examples are shown in Table 25.
[0204]
Table 23
[0205]
Table 24
[0206]
Table 25
[0207] Examples 11 to 41 showed that the flame retardant containing the dialkylphosphinic acid hybrid salt of the present invention has excellent flame retardancy efficiency for both polyamide and polyester. Comparative Example 1 showed that the flame retardancy efficiency of pure iron diethylphosphinate for polyamide and polyester is low. Comparative Examples 2 to 4 showed that the flame retardancy efficiency of pure aluminum diethylphosphinate for polyamide and polyester is low. Comparative Example 5 showed that the flame retardancy efficiency of pure aluminum diisobutylphosphinate for polyester is low. Comparative Example 6 showed that, at the same addition amount, the flame retardancy efficiency of pure aluminum diisobutylphosphinate for polyamide is inferior to that of the hybrid salt containing ethyl isobutylphosphinate. Refer to Examples 20, 26, 32 and 37. Also, according to the examples, for the hybrid salt containing diisobutylphosphinate, the higher the content, the darker the color of the flame-retarded sample and the more decomposition. The color of the polymer material sample obtained by flame retardancy of pure aluminum diisobutylphosphinate was the darkest.
[0208] The above are only some examples of the present application and are not intended to limit the present application in any form. Although the present application is disclosed as above in the preferred examples, they are not intended to limit the present application. Those skilled in the art can make minor changes or modifications using the technical content disclosed above without departing from the scope of the technical solution of the present application, which are equivalent to equivalent implementation examples and are included in the scope of the technical solution.
[0209] (Appendix) (Appendix 1) At least one selected from the compounds having the chemical formula shown in formula (I), [Chemical formula] However, M is the central atom, and diethylphosphinate ion, ethyl isobutylphosphinate ion, and diisobutylphosphinate ion are all ligands. M is selected from metal elements, and the metal element is at least one selected from Group IIA, IIIA, IVA, VA metal elements, transition metal elements, and lanthanide metal elements. n is the valence of metal M, and n is selected from 2, 3, or 4. It is characterized in that 0 ≦ x ≦ 0.95, 0.05 ≦ y ≦ 0.8, 0 ≦ z ≦ 0.5, and x + y + z = 1, and x + z > 0, which is a dialkylphosphinic acid hybrid salt.
[0210] (Appendix 2) The Group IIA metal element is at least one selected from Be, Mg, Ca, Sr, and Ba. The Group IIIA metal element is Al. The Group IVA metal element is Sn. The Group VA metal element is Sb. The transition metal element is at least one selected from Fe, Zn, Cu, Ti, Zr, and Mn. The lanthanide metal element is Ce. The dialkylphosphinic acid hybrid salt according to Appendix 1 is characterized by this.
[0211] (Appendix 3) It is characterized in that 0.03 ≦ x ≦ 0.87, 0.13 ≦ y ≦ 0.68, and 0 ≦ z ≦ 0.45. The dialkylphosphinic acid hybrid salt according to Appendix 1 is characterized by this.
[0212] (Appendix 4) It is characterized in that 0.03 ≦ x ≦ 0.7, 0.29 ≦ y ≦ 0.68, and 0.01 ≦ z ≦ 0.45. The dialkylphosphinic acid hybrid salt according to Appendix 3 is characterized by this.
[0213] (Appendix 5) The step of obtaining the dialkylphosphinic acid hybrid salt by causing Reaction I to occur in an aqueous phase with a material containing mixture A and a metal element source M is included. The mixture A contains diethylphosphinic acid and / or its alkali metal salt, ethylisobutylphosphinic acid and / or its alkali metal salt, and diisobutylphosphinic acid and / or its alkali metal salt, and is characterized in that it is a method for producing a dialkylphosphinic acid hybrid salt according to any one of Appendices 1 to 4.
[0214] (Appendix 6) The conditions of the reaction I are a temperature of 0 to 250 °C, a pressure of 0.1 MPa to 10 MPa, and a time of 0.1 to 20 h, and are characterized in that it is a production method according to Appendix 5.
[0215] (Appendix 7) The acquisition of the mixture A includes a step of introducing ethylene and isobutene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and performing reaction II to obtain the mixture A, and is characterized in that it is a production method according to Appendix 5.
[0216] (Appendix 8) The mass of water in the aqueous solution is 10 to 99% of the total mass of the radical initiator and phosphinic acid and / or its alkali metal salt, and is characterized in that it is a production method according to Appendix 7.
[0217] (Appendix 9) The conditions of the reaction II are a temperature of 0 to 250 °C, a time of 0.01 to 50 h, and a pressure of 0 to 3 MPa, and are characterized in that it is a production method according to Appendix 7.
[0218] (Appendix 10) The molar ratio of the radical initiator to the total amount of phosphinic acid and / or its alkali metal salt is 0.001 to 0.1:1, and is characterized in that it is a production method according to Appendix 7.
[0219] (Appendix 11) The acquisition of the mixture A Isobutene is introduced into an aqueous solution containing phosphinic acid and / or an alkali metal salt thereof and a radical initiator and reacted. After the molar ratio of the introduced isobutene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof reaches (y + 2z) / 1 of formula (I), the introduction of isobutene is stopped, and the introduction of ethylene is continued and reacted to obtain the mixture A, which is characterized in that it includes the step of the production method according to appended claim 7.
[0220] (Appended claim 12) The obtaining of the mixture A A part of isobutene and ethylene is introduced into an aqueous solution containing phosphinic acid and / or an alkali metal salt thereof and a radical initiator and reacted. The molar ratio of ethylene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof is smaller than (2x + y) / 1 of formula (I). After the molar ratio of the introduced isobutene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof reaches (y + 2z) / 1 of formula (I), the introduction of isobutene is stopped, and the introduction of the remaining ethylene is continued and reacted to obtain the mixture A, which is characterized in that it includes the step of the production method according to appended claim 7.
[0221] (Appended claim 13) The obtaining of the mixture A A part of ethylene is introduced into an aqueous solution containing phosphinic acid and / or an alkali metal salt thereof and a radical initiator, and the molar ratio of the part of ethylene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof is made smaller than (2x + y) / 1 of formula (I). After the part of ethylene has completely reacted, the introduction of isobutene is continued and reacted. After the molar ratio of the introduced isobutene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof reaches (y + 2z) / 1 of formula (I), the introduction of isobutene is stopped, and the introduction of the remaining ethylene is continued and reacted to obtain the mixture A, which is characterized in that it includes the step of the production method according to appended claim 7.
[0222] (Appended claim 14) The metal element source M is at least one selected from metal element M salts, which is characterized in that it is the production method according to appended claim 5.
[0223] (Appendix 15) A flame retardant, characterized in that it is selected from the dialkylphosphinic acid hybrid salts described in any one of Appendices 1 to 4.
[0224] (Appendix 16) A flame-retardant material comprising a flame retardant P and a thermoplastic polymer material, wherein the flame retardant P is at least one selected from the flame retardants described in Appendix 15.
[0225] (Appendix 17) The content of the flame retardant P in the flame-retardant material is 1 to 35% by mass, and the flame-retardant material described in Appendix 16 is characterized by this.
[0226] (Appendix 18) The flame-retardant material further comprises a functional additive, wherein the functional additive is at least one selected from a reinforcing agent, a drip inhibitor, a stabilizer, a pigment, a dye, a carbonization catalyst, a dispersant, a nucleating agent, an inorganic filler, and an antioxidant, and the flame-retardant material described in Appendix 16 is characterized by this.
[0227] (Appendix 19) The content of the functional additive in the flame-retardant material is 5 ~4 0 mass %, and the flame-retardant material described in Appendix 18 is characterized by this.
[0228] (Appendix 20) The flame-retardant material further comprises a flame retardant Q, wherein the flame retardant Q is at least one selected from a nitrogen-based flame retardant and a boron-based flame retardant, and the flame-retardant material described in Appendix 18 is characterized by this.
[0229] (Appendix 21) The content of the flame retardant Q in the flame-retardant material is 0.5 to 20% by mass, and the flame-retardant material described in Appendix 20 is characterized by this.
[0230] (Appendix 22) The flame-retardant material according to appended note 16, characterized in that the thermoplastic polymer material is at least one selected from polyamide and polyester.
Claims
1. At least one selected from compounds having the chemical formula shown in formula (I), 【Chemical 1】 wherein M is a central atom, and diethylphosphate ion, ethylisobutylphosphate ion, and diisobutylphosphate ion are all ligands, M is selected from metal elements, and the metal elements are at least one selected from Group IIIA metal elements and transition metal elements, n is the valence of metal M, and n is selected from 2, 3, or 4, 0.03 ≤ x ≤ 0.87, 0.13 ≤ y ≤ 0.68, 0 ≤ z ≤ 0.45, and x + y + z = 1, and x + z > 0, a dialkylphosphinic acid hybrid salt characterized by this.
2. The Group IIIA metal element is Al, The transition metal element is at least one selected from Fe, Zn, Cu, Ti, Zr, and Mn, the dialkylphosphinic acid hybrid salt according to Claim 1, characterized by this.
3. 0.03 ≤ x ≤ 0.7, 0.29 ≤ y ≤ 0.68, 0.01 ≤ z ≤ 0.45, the dialkylphosphinic acid hybrid salt according to Claim 1, characterized by this.
4. 0.5 ≤ x ≤ 0.7, 0.29 ≤ y ≤ 0.48, 0.01 ≤ z ≤ 0.21, the dialkylphosphinic acid hybrid salt according to Claim 3, characterized by this.
5. A step of obtaining the dialkylphosphinic acid hybrid salt by causing reaction I to occur in an aqueous phase with a material containing mixture A and a metal element source M, The mixture A includes diethylphosphinic acid and / or its alkali metal salt, ethylisobutylphosphinic acid and / or its alkali metal salt, and diisobutylphosphinic acid and / or its alkali metal salt, the method for producing a dialkylphosphinic acid hybrid salt according to any one of Claims 1 to 4, characterized by this.
6. The conditions of the reaction I are a temperature of 0 to 250 °C, a pressure of 0.1 MPa to 10 MPa, and a time of 0.1 to 20 h, the production method according to Claim 5, characterized by this.
7. The acquisition of the mixture A is A step of introducing ethylene and isobutene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator, and performing reaction II to obtain the mixture A, the production method according to Claim 5, characterized by this.
8. The mass of the water in the aqueous solution is 10 to 99% of the total mass of the radical initiator and the phosphinic acid and / or its alkali metal salt, and the production method according to claim 7 is characterized in that.
9. The conditions of the reaction II are a temperature of 0 to 250 ° C, a time of 0.01 to 50 h, and a pressure of 0 to 3 MPa, and the production method according to claim 7 is characterized in that.
10. The molar ratio of the radical initiator to the total amount of the phosphinic acid and / or its alkali metal salt is 0.001 to 0.1:1, and the production method according to claim 7 is characterized in that.
11. The acquisition of the mixture A is introducing isobutene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator and reacting them, and after the molar ratio of the introduced isobutene to the total phosphorus of the phosphinic acid and / or its alkali metal salt becomes (y + 2z) / 1 of the formula (I), stopping the introduction of isobutene and continuing the introduction of ethylene and reacting to obtain the mixture A, and the production method according to claim 7 is characterized in that it includes the steps of.
12. The acquisition of the mixture A is introducing isobutene and a part of ethylene into an aqueous solution containing phosphinic acid and / or its alkali metal salt and a radical initiator and reacting them, and when the molar ratio of ethylene to the total phosphorus of the phosphinic acid and / or its alkali metal salt is smaller than (2x + y) / 1 of the formula (I), and the molar ratio of the introduced isobutene to the total phosphorus of the phosphinic acid and / or its alkali metal salt becomes (y + 2z) / 1 of the formula (I), stopping the introduction of isobutene and continuing the introduction of the remaining ethylene and reacting to obtain the mixture A, and the production method according to claim 7 is characterized in that it includes the steps of.
13. The acquisition of the mixture A is A part of ethylene is introduced into an aqueous solution containing phosphinic acid and / or an alkali metal salt thereof and a radical initiator, and the molar ratio of the part of ethylene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof is made smaller than (2x + y) / 1 in the formula (I). After the part of ethylene has completely reacted, the introduction of isobutene is continued for reaction. After the molar ratio of the introduced isobutene to the total phosphorus of phosphinic acid and / or an alkali metal salt thereof becomes (y + 2z) / 1 in the formula (I), the introduction of isobutene is stopped, and the introduction of the remaining ethylene is continued for reaction to obtain the mixture A, the manufacturing method according to claim 7, characterized by including this step.
14. The manufacturing method according to claim 5, characterized in that the metal element source M is at least one selected from metal element M salts.
15. A flame retardant, characterized by being selected from the dialkylphosphinic acid hybrid salts according to any one of claims 1 to 4.
16. Including a flame retardant P and a thermoplastic polymer material, The flame-retardant material, characterized in that the flame retardant P is at least one selected from the flame retardants according to claim 15.
17. The flame-retardant material according to claim 16, characterized in that the content of the flame retardant P in the flame-retardant material is 1 to 35% by mass.
18. The flame-retardant material further includes a functional additive, The flame-retardant material according to claim 16, characterized in that the functional additive is at least one selected from a reinforcing agent, a drip inhibitor, a stabilizer, a pigment, a dye, a carbonization catalyst, a dispersant, a nucleating agent, an inorganic filler, and an antioxidant.
19. The flame-retardant material according to claim 18, characterized in that the content of the functional additive in the flame-retardant material is 5 to 40% by mass.
20. The flame-retardant material further includes a flame retardant Q, The flame-retardant material according to claim 18, characterized in that the flame retardant Q is at least one selected from a nitrogen-based flame retardant and a boron-based flame retardant.
21. The flame-retardant material according to claim 20, characterized in that the content of the flame retardant Q in the flame-retardant material is 0.5 to 20% by mass.
22. The flame-retardant material according to claim 16, characterized in that the thermoplastic polymer material is at least one selected from polyamide and polyester.
Citation Information
Patent Citations
Polydialkyl phosphinic acid metal composite salt and / or mixture thereof, and uses thereof
CN111825883A
Methods for preparing mixed substituted dialkylphosphinic acids, mixed substituted dialkylphosphinic acid esters, and mixed substituted dialkylphosphinate salts, and their uses.
JP2012512196A
Cited By
Dialkylphosphinic acid hybrid salts, method for preparing the same, and use thereof
JP2025521365A